2021
DOI: 10.1186/s13229-021-00461-7
|View full text |Cite
|
Sign up to set email alerts
|

Non-verbal IQ and change in restricted and repetitive behavior throughout childhood in autism: a longitudinal study using the Autism Diagnostic Interview-Revised

Abstract: Background Restricted and repetitive behavior (RRB) is one of the characteristic features of Autism Spectrum Disorder. This domain of symptoms includes a broad range of behaviors. There is a need to study each behavior individually to better understand the role of each in the development of autistic children. Moreover, there are currently no longitudinal studies investigating change in these behaviors over development. Methods The goal of the prese… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 53 publications
2
4
0
Order By: Relevance
“…Regarding RRB, recent studies showed that more RRB was present in adolescent boys than in younger groups of male children with ASD ( Van Wijngaarden-Cremers et al, 2014 ; Stroth et al, 2022 ). However, the current findings supported a recent longitudinal study showing a reduction in RRB with increasing age ( Courchesne et al, 2021 ). Specifically, using the ADI-R, Courchesne et al (2021) studied a population of 206 children at aged 6 and 8 years, respectively.…”
Section: Discussionsupporting
confidence: 91%
“…Regarding RRB, recent studies showed that more RRB was present in adolescent boys than in younger groups of male children with ASD ( Van Wijngaarden-Cremers et al, 2014 ; Stroth et al, 2022 ). However, the current findings supported a recent longitudinal study showing a reduction in RRB with increasing age ( Courchesne et al, 2021 ). Specifically, using the ADI-R, Courchesne et al (2021) studied a population of 206 children at aged 6 and 8 years, respectively.…”
Section: Discussionsupporting
confidence: 91%
“…Therefore, the diagnostic model constructed in this study is only suitable for children diagnosed with autism. For a long time, the relationship between RRBs and IQ has not reached a consensus ( 57 , 58 ). The diagnostic model constructed by ML in this study suggests that the higher the score of repetitive, stereotyped behavior in children with autism, the greater the possibility of combined ID.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to some prior work (Baribeau et al, 2021a; Gotham et al, 2013, 2014; Lidstone et al, 2014; Rodgers et al, 2012; Stratis & Lecavalier, 2013) we found little evidence for associations between RRBs and internalizing symptoms in autistic adults. By longitudinally characterizing change and stability in RRB subtypes from ages 2-19, this paper adds to previous work in this sample (Richler et al, 2010) as well as work conducted in other samples ((Bishop et al, 2013; Courchesne et al, 2021; McDermott et al, 2020; Uljarević et al, 2021) that have found differing profiles of RRB symptoms in autistic individuals both within and across age groups. This study also corroborates findings from other longitudinal samples that, on average, core ASD symptomology decreases with increasing age (Seltzer et al, 2004; Taylor & Seltzer, 2010).…”
Section: Discussionmentioning
confidence: 82%
“…Though few studies have examined RRBs longitudinally from early childhood to early adulthood, prior work in separate samples has examined changes in RRBs across childhood. Similar to Richler et al, (2010), these studies have found that many RRB behaviors increase from early to mid-childhood (Courchesne et al, 2021;Guthrie et al, 2013;Moore & Goodson, 2003). In contrast, cross-sectional studies of adults with ASD indicate RSM behaviors decrease with increasing age (Bishop et al, 2013;Esbensen et al, 2009;Evans et al, 2017;Uljarević et al, 2021).…”
Section: Developmental Characterizations Of Rrbsmentioning
confidence: 92%